Analysis Sincerity of Main Character in the Vow Movie Direct by Michael Sucsy - Zahira Alatas; Ira Miranti; R.R. Astri Indriana (JEdu: Journal of English Education, 2022)
The objective of this research is to reveal sincerity of main character in “The Vow” movie direct by Michael Sucsy. This research used qualitative method to obtain data through the way human’s things and behave as social being. This phenomenon is used as a group of data and analyzed for trends. The writer will analyze the data by using text analysis approach. Text analysis particularly oriented toward ethnography methods or grounded theory. It means that all the methods of test analysis which somehow approach texts by means of categories, since it no longer a matter only of the communicative content of the text but also their linguistic form. Based on the research sincerity of main character in The Vow movie direct by Michale Sucsy, the writer found 32 data invention which divides into 3 kinds of sincerity there are the noble high virtue in response to righteous request, the fundamental duty in response to lawful right, and sincerity of the utterly faithful by thought, feelings and desires. There are of the data,25% data of thought, 40% data of feelings, and 35% data of desires that found by the script in The Vow movie directed by Michale Sucsy.